An open-labelled randomized clinical trial for the evaluation of Balaharidradi Lepa with and without Khadira Twaka Kwath in Vyanga (Melasma) - Sukha Ram; Mita Kotecha; Krutika Jitendra Chaudhary (Wolters Kluwer Medknow Publications, 2021)
Introduction: Vyanga (Melasma) is a common disorder appearing on the face, causing skin discoloration. Niruja (painless), Tanu (thin), Shyava Varnayukta (hyperpigmentation), and Mandala (circular patches) are the peculiar diagnostic features of the disease. It is categorized as a Kshudra Roga (minor disease) in Ayurveda. Lepa (pack) and Kwath (decoction) are well-known medicines for Vyanga (Melasma). Balaharidradi Lepa and Khadira Twaka Kwath are defined as Vyangahara Dravyas in Ayurvedic Samhitas as they are having Vyangahara, Kushthaghna, Varnya, Krimighna, and Kantikara activity. This study aims to evaluate the effect of Balaharidradi Lepa with and without Khadira Twaka Kwath in Vyanga (Melasma). Materials and Methods: (i) Design: Open-labelled randomized clinical trial of thirty patients of either sex. (ii) Intervention: Group A (15 patients) was given Balaharidradi Lepa and Khadira Twaka Kwath, while Group B (15 patients) treated with Balaharidradi Lepa. (iii) Duration: 2 months. (iv) Outcome measures: photography. Results: All the two groups were compared by Kandu and Von luschan's color scale statistically significant results were observed in both Groups A and Group B. Conclusion: The present study supports the use of Balaharidradi Lepa and Khadira Twaka Kwath in treating Vyanga with the good acceptance by all treated patients.